EMU and European government bond market integration - Pilar Abad; Helena Chuliá; Marta Gómez-Puig (European Central Bank (ECB), 2009)
The main objective of this paper is to study whether the introduction of the euro had an impact on the degree of integration of European Government bond markets. We adopt the CAPM-based model of Bekaert and Harvey (1995) to compare, from the beginning of Monetary Union until June 2008, the differences in the relative importance of two sources of systemic risk (world and Eurozone risk) on Government bond returns, in the two groups of countries (EMU and non-EMU) in EU-15. Our empirical evidence suggests that the impact of the introduction of the euro on the degree of integration of European Government bond markets was important. The markets of the countries that share a monetary policy are less vulnerable to the influence of world risk factors, and more vulnerable to EMU risk factors. However, euro markets are only partially integrated, since they are still segmented and present differences in market liquidity or default risk. For their part, the countries that decided to stay out of the Monetary Union present a higher vulnerability to external risk factors.
Keywords: E44; F36; G15; 330; bond markets integration; Monetary integration; sovereign securities markets; Öffentliche Anleihe; Rentenmarkt; Marktintegration; CAPM; Eurozone; Eurozone; EU-Staaten